2020
DOI: 10.1128/aem.01448-20
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome-Engineered Lacticaseibacillus rhamnosus Strain GG Exhibits Cell Surface Glyceraldehyde-3-Phosphate Dehydrogenase Accumulation and Enhanced Adhesion to Human Colonic Mucin

Abstract: Differences in individual host responses have emerged as an issue in the health benefits of probiotics. Here, we applied ribosome engineering (RE) technology, developed in an actinomycetes study, to Lacticaseibacillus rhamnosus GG (LGG). RE can effectively enhance microbial potential by using antibiotics to induce spontaneous mutations in the ribosome and/or RNA polymerase. In this study, we identified eight types of streptomycin-resistant mutations in the LGG rpsL gene, which encodes ribosomal protein S12. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The mucosal layer serves as the primary interface between the intestinal tract and the members of the microbiota or probiotics before direct contact with the intestinal epithelium. For example, Lacticaseibacillus rhamnosus GG, the most studied probiotic lactic acid bacterium, is known to bind to mucin via glyceraldehyde-3-phosphate dehydrogenase (GAPDH) on its cell wall surface, and it has been reported that the binding strength varies depending on the amount of GAPDH [26]. Furthermore, the mucin within the intestinal mucosa not only functions as a scaffold for microbial adhesion but also serves as a nutrient source for bacterial proliferation [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…The mucosal layer serves as the primary interface between the intestinal tract and the members of the microbiota or probiotics before direct contact with the intestinal epithelium. For example, Lacticaseibacillus rhamnosus GG, the most studied probiotic lactic acid bacterium, is known to bind to mucin via glyceraldehyde-3-phosphate dehydrogenase (GAPDH) on its cell wall surface, and it has been reported that the binding strength varies depending on the amount of GAPDH [26]. Furthermore, the mucin within the intestinal mucosa not only functions as a scaffold for microbial adhesion but also serves as a nutrient source for bacterial proliferation [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Mucin functions as an adhesion receptor for surface GAPDH in lactobacilli [ 38 , 40 ]. Adhesion of lactobacilli to the intestine is partly due to the binding of GAPDH to human ABO-type blood group antigens expressed on human colonic mucin [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…An overnight culture of B. linens was centrifuged at 8,000× g for 5 min at 4°C. The obtained bacterial pellets were observed under a JSM 7600‐F SEM (JEOL, Tokyo, Japan) according to previously reported methods (Ishida et al, 2020; Tsukagoshi et al, 2020).…”
Section: Methodsmentioning
confidence: 99%